Mechanism of LncRNA Gm2044 in germ cell development - Zhu, Qinran; Sun, Junpei; An, Chuangchuang; Li, Xin; Xu, Shumin; He, Yutong; Zhang, Xinyi; Liu, Lei; Hu, Ke; Liang, Meng (Frontiers in Cell and Developmental Biology, 2024)
Germ cell development in mammals is a complex physiological process that involves the proliferation of primordial germ cells, meiosis, and the formation of male and female gametes. Long non-coding RNA (lncRNA) is a type of RNA with more than 200 nucleotides that does not code for proteins. A small number of lncRNAs have been shown to participate in spermatogenesis in the testes and in follicular development in the ovaries, but the role of the vast majority of lncRNAs and their molecular mechanisms still need further study. LncRNA Gm2044 was identified as a differentially expressed lncRNA in mouse spermatogenesis by microarray technology.In mouse testis, lncRNA Gm2044 can act as competing endogenous RNA to regulate SYCP1 expression in GC-2 cells derived from mouse spermatocyte cells, and it can also act as a host gene for miR-202 to regulate RBFOX2 protein expression. In female mouse ovaries, lncRNA Gm2044 regulates 17β-estradiol synthesis through the miRNA-138-5p-Nr5a1 pathway or by interacting with EEF2. In addition, studies suggest that lncRNA Gm2044 is also involved in the progression of reproductive system diseases such as male nonobstructive azoospermia. Here, we summarize the roles and molecular mechanisms of lncRNA Gm2044 in male and female gametogenesis and its potential role in some infertility disorders.